Differentiating Arteriolosclerotic Ulcers of Martorell from Other Types of Leg Ulcers Based on Vascular Histomorphology - Julia Deinsberger; Jonas Brugger; Philipp Tschandl; Barbara Meier-Schiesser; Florian Anzengruber; Simon Bossart; Stanislava Tzaneva; Peter Petzelbauer; Kornelia Böhler; Helmut Beltraminelli; Jürg Hafner; Benedikt Weber (Medical Journals Sweden, 2021)
Clinical differential diagnosis of arteriolosclerotic ulcers of Martorell is challenging due to the lack of clearly affirmative instrument-based diagnostic criteria. The aim of this study was to develop vascular histomorphological diagnostic criteria differentiating Martorell ulcers from other types of leg ulcers. The histomorphology of patients diagnosed with arteriolosclerotic ulcers of Martorell (n = 67) was compared with that of patients with venous leg ulcers, necrotizing leukocytoclastic vasculitis, pyoderma gangrenosum, and non-ulcerative controls (n = 15 each). In a multivariable logistic regression model, the rates of arteriolar calcification (odds ratio (OR) 42.71, 95% confidence interval (CI) 7.43-443.96, p < 0.001) and subendothelial hyalinosis (OR 29.28, 95% CI 4.88-278.21, p <0.001) were significantly higher in arteriolosclerotic ulcers of Martorell. Arteriolar cellularity was significantly lower in Martorell ulcers than in controls (OR 0.003, 95 CI < 0.001-0.97, p = 0.05). However, the wall-to-lumen ratio was similar in all ulcers (OR 0.975, 95% CI 0.598-2.04, p =0.929). Based on the Youden index, a wall cellularity of < 0.24 cells/100 μm2 was determined as the optimum cut-off point (sensitivity 0.955, specificity 0.944). Thus, arteriolar calcification, subendothelial hyalinosis, and arteriolar cellularity revealed high discriminatory power for arteriolosclerotic ulcers of Martorell.